Approximate Series Solution of Non Linear Fractional Dispersive Equations Using Generalized Differential Transform Method - Das, Deepanjan (International Journal of Computer Sciences and Engineering, 2019)
In the present paper, generalized differential transform method (GDTM) is used for obtaining the approximate analytic solutions of non-linear dispersive partial differential equations of fractional order. The fractional derivatives are described in the Caputo sense